The impact of internal control on the quality of financial reports - Case study: The Ministry of Finance in Ramallah - Sawafta, Othman Ahmed; Assassa, Samia Tawfeeq; Zedan, Shatha Mosa (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed at identifying the effect of internal control on the quality of financial reports. Case study: The Ministry of Finance in Ramallah. The study sample consisted of (50) workers in the Ministry of Finance, and they were randomly selected from the study population. A questionnaire was adopted to collect data, and the data were processed statistically by using the SPSS program. The study found a set of results: There is a statistically significant effect at the level of significance (0.05) for internal control in its dimensions (follow-up, information and communication) on the quality of financial reports in their dimensions, and the control Environment and risk assessment have been excluded, and employees' perceptions about the level of application of control came The Ministry of Finance has a high degree of interior, and their perceptions about the availability of the characteristics necessary to achieve quality in the financial reports were also high.The study recommended the necessity of studying monitoring and performance reports before making transfers between employees, and the need for the ministry to make strategic plans for risks so that rapid measures are taken to confront risks and get rid It also recommended the necessity of presenting clear and understandable financial information in order to increase the value of the financial reports in order to suit the users of those reports to make sound decisions.
Keywords: Internal Control; Quality of Financial Reports; Ministry of Finance